The California School and Beyond: How to Study the Great Divergence? - Vries, Peer (History compass, 2010)
In this article the autor presents a description, analysis and evaluation of the fundamentally new interpretation of the economic history of the early modern world that is defended by authors who collectively have become known as the California School, the most important among them being Kenneth Pomeranz, Roy Bin Wong, Andre Gunder Frank and Jack Goldstone. He in particular analyses their claim that in the period from roughly 1400 to 1800 the most advanced economies of Eurasia formed a world of ‘surprising resemblances’ and that the Great Divergence between ‘the West’ and ‘the Rest’ only originated with industrialisation and must be interpretated as a fairly contingent and recent phenomenon, basically due to differences in the availability of resources. The author claims that the Californians have a tendency to exaggerate the resemblances between Western Europe and East Asia and should be more specific when it comes to time, place and the differing historical trajectories of various regions. Finally, he claims they should pay far more attention to political and military developments and to the role of culture and institutions.